Influence of Dynamic Properties of Nonlinear Over-Voltage Limiter on Over-Voltage Limitation in Distribution Networks - A. N. Bokhan; V. V. Krotenok; S. N. Prokhorenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
One of the most efficient means of over-voltage reduction in arcing ground short-circuits is an application of   a nonlinear over-voltage limiter. It is necessary to take into account dynamic properties of the nonlinear over-voltage limiter in order to ensure authentic simulation of  over-voltage in the network A dynamic model of  the non-linear over-voltage limiter which takes a time lag constant   τ  into account during transition of the nonlinear over-voltage limiter into conducting state has been developed in the paper.